Научная школа Института сверхтвердых материалов им.В.Н.Бакуля НАН Украины - Малицкий, Б.А.; Кулаковский, В.Н. (Наука та наукознавство, 2011)
Описаны зарождение и развитие научной школы Института сверхтвердых материалов им. В.Н. Бакуля НАН Украины, вклад в появление, становление и деятельность школы ее основателей – В.Н. Бакуля и Н.В.Новикова. Приведены определение научной отрасли, в которой работает школа Бакуля–Новикова, основные научные результаты, полученные сотрудниками ИСМ. Характеризуются кадры школы и их исследования, работа с молодежью и связи с вузами, международные научные связи ИСМ, достижения и перспективы школы. Описано зародження і розвиток наукової школи Інституту надтвердих матеріалів ім. В.М.Бакуля НАН України, внесок у появу, становлення і діяльність школи її засновників — В.М.Бакуля і М.В.Новикова. Наведено визначення наукової галузі, в якій працює школа Бакуля—Новикова, основні наукові результати, отримані співробітниками ІСМ. Характеризуються кадри школи та їх дослідження, робота з молоддю і зв’язки з вузами, міжнародні наукові зв’язки ІСМ, досягнення і перспективи школи. Detailed descriptive and statistical information is contained about fields and results of S&T and manufacturing in the Institute for Super Hard Materials (ISHM), which was created in Kiev on July 6, 1961, due to specific technological needs of the Soviet industry and, therefore, had to perform the task being not common for traditional academic institutions – technical development and launch of mass-scale production of synthetic diamond powders and instruments made thereof. The individual contributions of its two directors is shown: V.N.Bakul (1961-1977) as the founder of its production and research facility, and N.V.Novikov (since 1977 and on), which, having kept all the traditions laid by V.N.Bakul, could enhance the style and methods of team work and develop the earlier established academic school. A description of the scientific branch in which this school is engaged is given.